NAFKAH PRODUKTIF UNTUK ANAK PERSPEKTIF KIAI SYANSURI BADAWI - Yayan Musthofa; Mohamad Anang Firdaus (Asy-Syari'ah, 2022)
Abstract: The obligation of parents to provide for their children at least until they reach adulthood, which is 21 years referring to the KHI policy article 98 paragraph (1), when they are married, or have entered ar-rusydu phase (understanding the law and independence) referring to classical fiqh studies. In another study on maqāshid as-syarī'ah version, when the child has entered the age of 23 years based on the calculation finishing study period plus a year of financial independence trial period. In order to study further to prepare children's financial independence, this study aims to examine more deeply the concept of productive livelihood from the maqāsid as-syarī'ah perspective in the book of Fiqh Al-Munākaḥāt by Kiai Syansuri Badawi. This article includes a literature review with the maqāsid as-syarī'ah approach of Jasser Auda, while the object of this study is the work of Kiai Syansuri Badawi. From this research, I found that livelihood in Kiai Syansuri Badawi's view contains a productive meaning or a productive spirit and is in accordance with Jasser Auda's maqāshid as-syarī'ah concept for human development as the goal of the Shari'a. This article is important to build human development –especially Muslims– with the disteribution and management of a productive living, starting from the smallest organization, namely the family.Abstrak: Kewajiban orangtua menafkahi anak setidaknya berlangsung hingga masuk usia dewasa, yakni 21 tahun bila merujuk kebijakan KHI PPasal 98 ayat (1), ketika sudah menikah, atau sudah masuk fase ar-rusydu (cakap hukum dan mandiri) bila merujuk kajian fikih klasik. Dalam kajian lain versi maqāsid as-syarī’ah, ketika anak sudah masuk usia 23 tahun dengan perhitungan usai masa belajar ditambah setahun masa uji coba kemandirian finansial. Untuk mengkaji lebih lanjut untuk menyiapkan kemandirian finansial anak, penelitian ini bertujuan untuk mengkaji lebih dalam konsep nafkah produktif perspektif maqāshid as-syarī’ah dalam kitab Fiqh Al-Munākaḥāt karya Kiai Syansuri Badawi. Artikel ini termasuk kajian pustaka dengan pendekatan maqāshid as-syarī’ah Jasser Auda, sedangkan objek kajiannya adalah karya Kiai Syansuri Badawi. Dari kajian tersebut, peneliti mendapatkan hasil bahwa nafkah dalam pandangan Kiai Syansuri Badawi mengandung makna produktif atau spirit-produktif dan sesuai dengan konsep maqāshid as-syarī’ah Jasser Auda untuk pengembangan SDM (human development) sebagai tujuan dari syariat. Artikel ini penting guna membangun human development –khususnya umat Islam– dengan penyaluran dan pengelolaan nafkah menjadi produktif, dimulai dari organisasi terkecil, yakni keluarga.